Obesity increases the prevalence and the incidence of asthma and worsens asthma severity - R. Barros (2017)
Background & aims: We aimed to explore the association between obesity and asthma prevalence, incidence and severity.Methods: The study included 32,644 adults, 52.6% female, from a representative sample of the 4th Portuguese National Health Survey. The following asthma definitions were used: ever asthma (ever medical doctor asthma diagnosis), current asthma (asthma within the last 12 months), current persistent asthma (required asthma medication within the last 12 months), current severe asthma (attending an emergency department because of asthma within the last 12 months), and incident asthma (asthma diagnosis within the last 12 months). Body mass index was calculated based on self-reported weight and height and categorised according to WHO classification. Logistic regression models adjusted for confounders were performed.Results: Prevalence of ever asthma was 5.3%, current asthma 3.5%, current persistent asthma 3.0%, currentsevere asthma 1.4%, and incident asthma 0.2%. Prevalence of obesity was 16%, overweight 37.6%,normal weight 44.6% and underweight 0.2%. Being overweight, obesity class I and II, and obesity class IIIwere associated with an OR (95% CI) with ever asthma 1.22 (1.21e1.24), 1.39 (1.36e1.41), 3.24 (3.08e3.40) respectively; current asthma 1.16 (1.14e1.18), 1.86 (1.82e1.90), 4.73 (4.49e4.98) respectively;current persistent asthma 1.08 (1.06e1.10), 2.06 (2.01e2.10), 5.24 (4.96e5.53), and current severe asthma1.36 (1.32e1.40), 1.50 (1.45e1.55) and 3.70 (3.46e3.95), respectively. Considering the incidence ofasthma, obesity more than quadrupled the odds (OR 4.46, 95% CI 4.30, 4.62).Conclusion: Obesity is associated in a dose dependent way with an increase of prevalent and incident asthma, and it seems to increase the odds of a more persistent and severe asthma phenotype independently of socio-demographic determinants, physical activity, and dietary patterns. Our results provide rational for future lifestyle intervention studies for weight reduction in the obesityeasthma phenotype.